Assessment of Response Strategy in Mega Construction Projects - Mashali, Ayman; Elbeltagi, Emad; Motawa, Ibrahim; Elshikh, Mohamed (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Mega Construction Projects (MCPs) that are executed unavoidably face several of the organizational challenges and pressures. Due to the stakeholder pressures in the execution of MCPs, organizations may adopt various strategic responses. Purpose – The objective of this paper is to investigate the common response strategies (RSs) applied in MCPs in the State of Qatar, in addition to overcoming the construction problems and enhance performance during the construction stage. Design/methodology/approach – A questionnaire survey is carried out among the most important firms in construction industry in Qatar. Three steps are used to finalize and evaluate the questionnaire before proceeding with the full survey, validity, pre-testing and pilot study. Quantitative data analysis is carried through the Statistical Package for Social Science software (SPSS). Findings – Results define and demonstrate five different types of RSs. They are ranging from passive to active strategies determined by project organization. The RSs include: adaptation strategy, avoidance strategy, compromising strategy, dismissal strategy, and influence strategy. Originality/value – This paper identifies and evaluates the RSs in MCPs that could potentially improve project team more efficiently and effectively.